High temperature micromechanical behavior of Ti2AlN particle reinforced TiAl based composites investigated by in-situ high-energy X-ray diffraction - Jinguang Li (Elsevier, 2021)
The high-temperature compressive property of Ti2AlN/TiAl composites, which are promising lightweight materials for high-temperature applications, was investigated. In situ high-energy X-ray diffraction (HEXRD) was utilized to analyze the micromechanical behavior at different deformation stages. It is determined {110}γ fiber texture firstly formed at work hardening stage and {0002}H fiber texture appeared at softening stage. The micro-deformation sequences were related to crystallographic orientations where [200]//LD, [202]//LD oriented γ grains were easier to work-hardening while [002]//LD, [110]//LD oriented γ grains presented hardening-softening transformation characteristic. The lattice strain wave of [0002]//LD oriented H grain reflected an interesting atomic-scale ripples meanwhile [10_13]//LD oriented H phase presented a unique interface-dislocation mechanism. A significantly higher stress level in H phase demonstrates its strong bearing capacity. Our investigations establish a relationship between macroscopic deformation of composite and the microscopic elastic/plastic deformation of each component meanwhile provide in-depth understanding of the cooperative deformation characteristics in Ti2AlN/TiAl composites.